Healthcare professionals' perceptions of the facilitators and barriers to implementing electronic systems for the prescribing, dispensing and administration of medicines in hospitals: a systematic review. Issue 6 (10th August 2015) - Hogan-Murphy, Diana; Tonna, Antonella; Strath, Alison; Cunningham, Scott
Abstract : Objective: To identify, critically appraise, synthesise and present the available evidence on healthcare professionals' perceptions of the facilitators and barriers to implementing electronic prescribing, dispensing and/or administration of medicines in the hospital setting. Methods: A systematic search of studies focusing on healthcare professionals' perceptions of technologies for prescribing, dispensing and administering medicines in the hospital setting was performed using MEDLINE, Cumulative Index to Nursing and Allied Health, International Pharmaceutical Abstracts, PsycARTICLES, PsycINFO, Cochrane Database of Systematic Reviews and Centre for Reviews and Dissemination. Grey literature inclusive of manual searching of core journals, relevant conference abstracts and online theses were also searched. Independent duplicate screening of titles, abstracts and full texts was performed by the authors. Data extraction and quality assessment were undertaken using standardised tools, followed by narrative synthesis. Key findings: Five papers were included in the systematic review after screening 2566 titles. Reasons for exclusion were duplicate publication; non-hospital setting; a lack of investigation of healthcare professionals' perceptions and a lack of focus on implementation processes or systems specific to electronic prescribing, dispensing or administration of medicines. Studies were conducted in the USA, Sweden and Australia. All studies used qualitative interview methods. Healthcare professionals perceived systems improved patient safety and provided better access to patients' drug histories and that team leadership and equipment availability and reliability were essential for successful implementation. Key barriers included hardware and network problems; altered work practices such as time pressure on using the system and remote ordering as a potential risk for errors; and weakened interpersonal communication between healthcare professionals and with patients. Conclusions: Few studies were identified on healthcare professionals' perceptions of the facilitators and barriers to system implementation in hospitals. Key facilitators included a perception of increased patient safety and better access to patients' drug history while key barriers involved technical problems, changes to routine work practices and weakened interpersonal communication. Investigating this area further will assist in improving patient safety and reducing medication costs by informing and strengthening implementation strategies.